Development of a test device for the evaluation of journal bearings - Sandvik, K; Lehtovaara, A; Makkonen, E; Kallio, M; Kuvaja, K; Kuokkala, V-T (Tribologia - Finnish Journal of Tribology, 2017)
Journal and thrust bearings are widely used in heavy industry. Today, there is a growing need for studying different kinds of new bearing material and coating solutions in operating conditions where full film lubrication cannot be achieved or sustained. A test device for the evaluation of journal bearings was developed. The device consists of a rotating shaft and four stationary test bearings. This scheme eliminates the need for support bearings, allowing an accurate measurement of friction. The initial tests were carried out with a variety of loads and sliding speeds in mixed and full film regimes. The friction results in the form of a Stribeck curve were obtained and found to be in line with general trends. The results also indicate that the bearing lift-off speed occurs when the value of the non-dimensional ηen / ppro - parameter is in the range of 0.5·10-8 - 1.0·10-8.